2017
DOI: 10.1038/s41598-017-02915-6
|View full text |Cite
|
Sign up to set email alerts
|

Innate And Adaptive Immunity are Progressively Activated in Parallel with Renal Injury in the 5/6 Renal Ablation Model

Abstract: The mechanisms triggering renal inflammation in chronic kidney disease (CKD) are unclear. We performed a detailed analysis of the time course of innate and adaptive immunity activation in the 5/6 renal ablation (Nx) model. Munich-Wistar rats undergoing Nx were studied 15, 60 and 120 days after ablation. Hypertension, albuminuria, creatinine retention, interstitial expansion and infiltration by macrophages and T-lymphocytes were already evident 15 days after Nx. PCR-array was used to screen for altered gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
18
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 63 publications
6
18
0
4
Order By: Relevance
“…The NLRP3 inflammasome is another innate immunity pathway activated in CKD [2,3]. Recently, we showed that the renal [1]. Accordingly, we showed in the present study that the renal content of NLRP3 and mature caspase 1 was elevated 60 days after Nx, in association with increased IL-1β protein content, which exerts a proinflammatory effect in the renal tissue, promoting enhanced cytokine production and macrophage recruitment.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The NLRP3 inflammasome is another innate immunity pathway activated in CKD [2,3]. Recently, we showed that the renal [1]. Accordingly, we showed in the present study that the renal content of NLRP3 and mature caspase 1 was elevated 60 days after Nx, in association with increased IL-1β protein content, which exerts a proinflammatory effect in the renal tissue, promoting enhanced cytokine production and macrophage recruitment.…”
Section: Discussionsupporting
confidence: 59%
“…CKD is characterized by progressive proteinuria, hypertension, chronic inflammation and oxidative stress that lead to loss of renal function and fibrosis. Recently we showed that renal inflammasome activation occurs as early as fifteen days after 5/6 renal ablation (Nx), and persists through advanced phases of this CKD model [1]. Additional recent observations suggest that renal inflammasome is activated in patients with CKD and in animal models of this condition [2−5], and that its deficiency prevents kidney injury [6].…”
Section: Introductionmentioning
confidence: 99%
“…We have recently demonstrated that innate and acquired immunity are activated in parallel in the Nx model [ 9 ]. Other studies provided a possible mechanistic explanation for this link by showing that NLRP3 is expressed in CD4 lymphocytes, acting as a transcription factor [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that nearly simultaneous activation of both innate and adaptive immunity occurs soon after 5/6 renal ablation (Nx) [ 9 ], persisting throughout the evolution of this CKD model. Other recent clinical and experimental observations have also suggested that innate immunity is activated in the setting of kidney disease [ 10–14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic inflammation can cause irreversible glomerular and tubular injury and renal functional loss. In 5/6 nephrectomy Munich-Wistar rats, macrophage infiltration is evident after ablation, the NLRP3 inflammasome is activated, and M1 macrophage-related gene expression is increased; furthermore, the glomerulosclerosis index is significantly higher with a progressive increase in albuminuria, creatinine retention, and higher blood pressure compared to the control rats [ 47 ]. In nephrocalcinosis-related CKD mice, deposition of oxalate crystal and tubular injury are associated with activation of NLRP3 inflammasomes; inhibition of NLRP3 induces a shift of macrophages from CD45 + F4/80 + CD11b + CX3CR1 + CD206 − , an M1 pro-inflammatory state, to CD45 + F4/80 + CD11b + CD206 + TGFβ − , an M2 anti-inflammatory phenotype, and attenuates the progression of CKD [ 48 ].…”
Section: Introductionmentioning
confidence: 99%